2019
DOI: 10.1101/868448
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phagocytic glia are obligatory intermediates in transmission of mutant huntingtin aggregates across neuronal synapses

Abstract: 14Emerging evidence supports the hypothesis that pathogenic protein aggregates associated with 15 many neurodegenerative diseases spread from cell to cell through the brain in a manner akin to 16 infectious prions. Here, we show that mutant huntingtin (mHtt) aggregates associated with Huntington 17 disease transfer anterogradely from presynaptic to postsynaptic neurons in the adult Drosophila 18 olfactory system. Trans-synaptic transmission of mHtt aggregates is inversely correlated with neuronal 19 activity a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 104 publications
1
9
0
Order By: Relevance
“…In a landmark study in Drosophila , it was shown that mHTT exon 1 tagged with mCherry shuttles from neurons to neighbouring phagocytic glia and forms aggregates with endogenous HTT in glia 56 . Other studies showed that mHTT can be exchanged between brain cells in Drosophila , in mice 5759 , and even in humans as mHTT aggregates were detected in healthy embryonic neurons grafted in the brain of Huntington’s disease patients 60 . mHTT can be packaged in exosomes of different cell types 61, 62 and be taken up by neighbouring cells, including neurons.…”
Section: Discussionmentioning
confidence: 99%
“…In a landmark study in Drosophila , it was shown that mHTT exon 1 tagged with mCherry shuttles from neurons to neighbouring phagocytic glia and forms aggregates with endogenous HTT in glia 56 . Other studies showed that mHTT can be exchanged between brain cells in Drosophila , in mice 5759 , and even in humans as mHTT aggregates were detected in healthy embryonic neurons grafted in the brain of Huntington’s disease patients 60 . mHTT can be packaged in exosomes of different cell types 61, 62 and be taken up by neighbouring cells, including neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Astrogliosis, or the proliferation of immune active astrocytes, is typically observed at later stages of HD (Al-Dalahmah et al, 2020;Buscemi et al, 2017). These immune-activated glia not only eliminate synapses (Liddelow et al, 2017;Sofroniew, 2009) but can also transmit mHTT aggregates through the synapse (Donnelly et al, 2020). In Drosophila, knockdown of draper prevents astrocytic phagocytosis and stops the spread of mHTT protein aggregates from pre-synaptic neurons to the post-synaptic compartment (Donnelly et al, 2020;Pearce et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…These immune-activated glia not only eliminate synapses (Liddelow et al, 2017;Sofroniew, 2009) but can also transmit mHTT aggregates through the synapse (Donnelly et al, 2020). In Drosophila, knockdown of draper prevents astrocytic phagocytosis and stops the spread of mHTT protein aggregates from pre-synaptic neurons to the post-synaptic compartment (Donnelly et al, 2020;Pearce et al, 2015). mHTT protein can also enter the synaptic space by endosomal/lysosomal secretion mediated by Syt7 (Trajkovic et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are now not only recognized as victims, but also as a source of non-cell autonomous toxicity. Microglia, the CNS residing macrophages, were shown to be involved in the spreading of several prion-like proteins [ 149 , 150 , 151 , 152 , 153 ]. Moreover, the uptake of toxic protein species might facilitate microglia activation and lead to neuroinflammation, which is implicated in several neurodegenerative diseases [ 154 ].…”
Section: C Elegans Models To Study Prion-like mentioning
confidence: 99%